2015
DOI: 10.5489/cuaj.2248
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting complications according to the modified Clavien classification in complete supine percutaneous nephrolithotomy

Abstract: Cite as: Can Urol Assoc J 2015;9(1-2):e83-92. http://dx.doi.org/10.5489/cuaj.2248 Published online February 9, 2015. AbstractIntroduction: An increase in percutaneous nephrolithotomy (PCNL) has been accompanied by an increase in complications. We identified the parameters affecting the severity of complications using the modified Clavien classification (MCC). Methods: From 2008 to 2013, 330 patients underwent complete supine PCNL using subcostal access, one-shot dilation, rigid nephroscopy, and pneumatic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The difference was not significantly different, although this may be because of highly heterogeneity between the studies. Also, in adults, Falahatkar et al (17) showed renal dysfunction, upper urinary tract abnormality, significant hydronephrosis, multiple tracts, post-operative hemoglobin and hemoglobin drop predicted complications and as a consequence, the length of hospital stay. Some of these predicted complications were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The difference was not significantly different, although this may be because of highly heterogeneity between the studies. Also, in adults, Falahatkar et al (17) showed renal dysfunction, upper urinary tract abnormality, significant hydronephrosis, multiple tracts, post-operative hemoglobin and hemoglobin drop predicted complications and as a consequence, the length of hospital stay. Some of these predicted complications were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…2 Nevertheless, lower calyceal access and single-tract accesses are associated with a lower complication rate and shorter hospital stay. 3,4 Thus, combining the safety of a single lower calyceal tract with high SFRs would be an optimal scenario. The aim of the present study is to evaluate the effectiveness and safety of single lower calyceal tract combined with flexible nephroscopy for the management of staghorn renal stones by PCNL.…”
Section: Introductionmentioning
confidence: 99%
“…Positive preoperative urine culture or preexisting UTI were reported by several authors as a significant parameter predicting complications (8-10): according to other studies (11,12) we have not founded this correlation with complications. Few studies investigated the correlation between normal or impaired renal function and onset of complications with discordant results: Yaycioglu (13) reported no difference, while Sairam and Falahatkar (14,15) showed a significantly increased complication rates associated to chronic kidney disease. In our study, only four patients were affected by impaired renal function pre PCNL, and with a postoperative progress in line with other patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the study leaded by Shin stone' s size and staghorn or complex stone had a significant influence only in minor complications, such as UTI or pain (20). Some studies (9,15), one of the most recent was published on February 2015 by Falahatkar et al (15) reported the PCNL complications according to the modified Clavien system (MCC), a scale that allows to classify complications basing on life-treating condition, interventions required, and disability. Nevertheless the MCC cannot predict, as said by the same authors, the occurrence of a specific complication and cannot reveal its reason.…”
Section: Discussionmentioning
confidence: 99%